High efficiency near-infrared light emission and ultra-high stability of the lead-free double perovskite Cs2Na1−xAgxBi1−yAlyCl6. Issue 41 (28th September 2022) - He, Bin; Wei, Qilin; Ke, Bao; Wu, Zixuan; Zhao, Hualin; Wei, Jieyu; Yang, Chengzhi; Jin, Shuya; Zou, Bingsuo
Abstract : Co-Doping with Al and Ag ions modifies the band structure of Cs2 NaBiCl6 to give strong near-infrared emission. Abstract : Environmentally friendly lead-free double perovskites with good stability can solve the problems of toxicity and instability of lead halide perovskites and can be a powerful substitute for them. In this study, Cs2 Na1− x Ag x Bi1− y Al y Cl6 perovskite powders co-doped with Ag + and Al 3+ were synthesized using a simple hydrothermal method. They can emit bright and wide near-infrared light, with the center at 715 nm, and the photoluminescence quantum yield is as high as 48.6%. This bright emission results from the combined modification effects of self-trapped exciton (STE) formation, carrier incorporation by Ag + and the carrier spatial confinement by the Al ions on the indirect band of Cs2 NaBiCl6 . In addition, Cs2 Na1− x Ag x Bi1− y Al y Cl6 also shows ultra-high structural stability and good thermal stability with a melting point of up to 600 °C. Our work not only opens up a new way for the design of efficient and stable near-infrared light-emitting materials with an atomic level confining modification, but also may have great applications in the fields of optical communication and quantum storage, as well as in near-infrared detection of the human body.